ACSM's clinical exercise physiology - Thompson, Walter R. PhD, FACSM, ACSM-CEP, RCEP, PD; Ozemek, Cemal PhD, FACSM, ACSM-CEP (Wolters Kluwer, 2025)
The logical presentation of material provides a format that can be used over the course of one to two semesters in any college or university offering advanced undergraduate or graduate classes in clinical exercise physiology. Organized in semisequential manner, the first chapter details the history of clinical exercise physiology. The second chapter provides an overview of the life cycle from birth to death with a special focus on women and children. After these two introductory chapters, the book builds sequentially, each chapter increasingly become more independent. Chapters 3 and 4 review the benefits and risks associated with exercise and physical activity and introduce preparticipation health screening, followed by a detailed description of how to develop exercise programs for the apparent healthy client. These chapters provide the foundation for subsequent topics that are more specific, such as cardiovascular disease, respiratory disease, diabetes, physical and intellectual impairments, cancer, diseases and conditions of the bones and joints, immunological disorders, and behavior and mental health as they relate to exercise. Chapter 16 focuses on multiple disorders (co- or multimorbidities), followed by environmental and genetic impacts. The final chapter describes and outlines potential legal issues facing the CEP